Prohibition of Eugenic Practices in Europe: Political and Legal Reasons - E. A. Torkunova (Московский журнал международного права, 2025)
INTRODUCTION. This article is devoted to the analysis of the complex political and legal reasons behind the prohibition of eugenics in European law. The article examines the contemporary prohibition of eugenics in the Charter of Fundamental Rights of the European Union 2000, the ban in international criminal law, the historical regulation of eugenic practices in European countries, as well as new challenges in this area.MATERIALS AND METHODS. The scientific study examines international treaties, conventions, and judicial practice. General scientific and specific scientific methods of cognition (methods of analysis and synthesis, deduction, induction, comparative legal and formal legal methods) were used in preparing the study.RESEARCH RESULTS. The author concludes that there are several blocks of reasons for the modern prohibition on the regulation of eugenic practices. The first block of reasons for the prohibition of eugenics is linked to the criminalization of certain eugenic practices, including the deliberate selection of people, at the international level after World War II. The second block of the eugenics ban is due to the failure of the political and legal course in several European countries (primarily Scandinavia), associated with the infringement of reproductive rights of certain vulnerable social groups. The third block of reasons for the prohibition of eugenics is triggered by attempts to apply modern advances in biomedicine and genetics, affecting human reproduction and genome, which could adversely impact the interests of future generations of humanity.DISCUSSION AND CONCLUSIONS. New challenges of eugenics are difficult to regulate and are often not covered by any prohibition or legal regulation at all. An obvious threat is that eugenics for the purpose of human selection, facilitated by the development of new biotechnologies, may become an initiative of civil society without any state programs and policies and be based on the activities of non-state actors or the convictions of private individuals.